Perubahan Bentuk Planlet Pisang Raja Sereh Hasil Mutasi dengan Ethyl Methane Sulphonate (EMS) Secara In Vitro - Yanti, Yulmira; Habazar, Trimurti; ', Mardinus; ', Mansyurdin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
The shoot of “rajasereh” banana was treated by 0,2% and 0,5% of ethyl methane sulfonate (EMS), for 2 and 4 hoursthourgh in vitro. The results showed that treatment of EMS mutagen would be changed morphologycal characterseither in planlet. In planlet stage was obtained four morphololgycal variations. One of the variant have characterizedthe colour yellowish; the leaves and stem are yellowish: the leaves were small and spiral. The value of coefficientof variant for morfphologycal characters of planlet “raja sereh” banana increased compare to the control. Theextreme value of coefficient of variant in planlet stage was found the times shoots is 84,31%, while control that is8,24%. EMS mutagen could caused several planlets shorter, total of leaves could of shoot are mostly